Global environmental flow information for the sustainable development goals - Sood, Aditya; Smakhtin, Vladimir U.; Eriyagama, Nishadi; Villholth, Karen G.; Liyanage, Nirosha; Wada, Y.; Ebrahim, Girma Yimer; Dickens, Chris (International Water Management Institute, 2017)
Environmental flows (EF) are an important component of Goal 6 (the ‘water goal’) of the Sustainable Development Goals (SDGs). Yet, many countries still do not have well-defined criteria on how to define EF. In this study, we bring together the International Water Management Institute’s (IWMI’s) expertise and previous research in this area to develop a new methodology to quantify EF at a global scale. EF are developed for grids (0.1 degree spatial resolution) for different levels of health (defined as environmental management classes [EMCs]) of river sections. Additionally, EF have been separated into surface water and groundwater components, which also helps in developing sustainable groundwater abstraction (SGWA) limits. An online tool has been developed to calculate EF and SGWA in any area of interest.